2021
DOI: 10.1101/2021.02.11.430712
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Substrates modulate charge-reorganization allosteric effects in protein-protein association

Abstract: Protein function may be modulated by an event occurring far away from the functional site, a phenomenon termed allostery. While classically allostery involves conformational changes, we recently observed that charge redistribution within an antibody can also lead to an allosteric effect, modulating the kinetics of binding to target antigen. In the present study, we study the association of a poly-histidine tagged enzyme (phosphoglycerate kinase, PGK) to surface-immobilized anti-His antibodies, finding a signif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(24 reference statements)
1
3
0
Order By: Relevance
“…The findings here, combined with previous studies (10, 11), point to a new role of charge reorganization, or of polarizability, in modulating protein activities. Surprisingly, not much is known about the involvement of polarizability in protein function, though the development of polarizable force fields for molecular dynamics simulations of biomolecules in recent years may change this situation(19).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The findings here, combined with previous studies (10, 11), point to a new role of charge reorganization, or of polarizability, in modulating protein activities. Surprisingly, not much is known about the involvement of polarizability in protein function, though the development of polarizable force fields for molecular dynamics simulations of biomolecules in recent years may change this situation(19).…”
Section: Discussionsupporting
confidence: 80%
“…Due to their internal conformational dynamics, as well as the presence of titratable side chains, proteins may possess significant polarizability values. Recent computational work from Takano and coworkers [6][7] , and experimental work from our labs [8][9] has indeed hinted at a role for charge reorganization as an allosteric signal in proteins. Here we decisively establish this role by studying the effect of phototriggered charge injection on both protein-protein association kinetics and enzyme kinetics.…”
mentioning
confidence: 93%
“…Ghosh et al further reported that the degree of binding modulation may be tuned through control of the dipole moment across the binding antigen. 68 The unmodified antigen used in the experiments described thus far binds to the surfacetethered antibody at its positively charged C-terminus. However, upon binding a negatively charged substrate molecule, the dipole moment across the antigen was found to decrease, thus reducing the induced charge redistribution across the antibody.…”
Section: Chiral-induced Spin Selectivity: Recent Advancesmentioning
confidence: 98%
“…Due to the CISS effect, the spin polarization of a chiral molecule, such as a protein, can be influenced by interacting or binding it to a magnetized surface. 23,24 Spin distribution in a protein can be altered by controlling the magnetization of the surface to which it is adsorbed, owing to a compensational response to spin exchange interactions between the protein and the surface. 21 Moreover, chiral molecules themselves can orient paramagnetic surface magnetization according to their preferred spin direction.…”
Section: Introductionmentioning
confidence: 99%